Blue light activates calcium-permeable channels in Arabidopsis mesophyll cells via the phototropin signaling pathway. - Dietrich, Petra; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2003)
Light is a central regulator of plant growth and development. Among the processes triggered by blue and UV-A light, phototropism, stomatal movement, and chloroplast orientation rely on the activation of blue-light receptors known as phototropins. So far, these photoreceptors constitute a class of light receptor kinases unique to the plant kingdom. In Arabidopsis thaliana, the two members phot1 and phot2 have been shown to display partially overlapping functions. Up to now little is known about the signaling cascade, which links these phototropins to the physiological responses downstream of blue-light perception. Here, we show that on illumination with blue light, but not red light, voltage-dependent and calcium-permeable channels activate in the plasma membrane of mesophyll cells. Blue-light stimulation in the presence of the photosynthetic electron transport inhibitor, 3-(3,4-dichlorophenyl)-1,1-dimethylurea, indicates that blue-light receptors rather than photosynthesis control channel activity. Sensitivity toward the protein kinase inhibitor K252a further pointed to the possible involvement of light receptor kinases. In support of this hypothesis, in the photoreceptor mutant phot1-5, blue-light induction of calcium currents was dramatically reduced and was eliminated in the double mutant phot1-5 phot2-1. By contrast, in cry1-304 cry2-1, an Arabidopsis mutant lacking another class of plant blue-light receptors, the channel remained sensitive to blue light. We thus conclude that blue light triggers calcium fluxes via the phototropin-activated calcium-permeable channel.